Zakat contribution model in entrepreneurship empowerment of zakat institutions: Case study of Lazismu Pusat - Sutrisno; Razali Haron (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
This study aims to find out how the strategy of distribution implemented by Muhammadiyah Zakat Management Institution (Lazismu) in the entrepreneurship empowerment program and zakat distribution program for zakat recipients. The method in this study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation, with validity using a triangulation model. Sampling was focused on the distribution of the entrepreneurship empowerment program for the 2021 period. The sample studied was the zakat manager and 8 zakat recipients of the empowerment program. This study shows that financial assistance in the form of zakat funds can increase the income and economy of most recipients. Accordingly, this program helped the community to improve the business and realize the main goal of productive zakat, namely increasing the economy of zakat recipients and adding new zakat givers and new zakat recipients. Furthermore, the main objective is to develop and advance the economy of the poor zakat recipients. The solution offered regarding the problems faced by Zakat recipients is to maximize the role of the Leaders in monitoring and empowering zakat recipients on an ongoing basis. In addition, monitoring and supervision are carried out by holding regular recitations for zakat recipients